Epidemiology of Traumatic brain injury in Ethiopia: A systematic review and meta-analysis of prevalence, mechanisms, and outcomes - Yohannis Derbew Molla; Hirut Tesfahun Alemu (PLoS ONE, 2025)
Introduction Traumatic brain injury (TBI) is a major cause morbidity and mortality globally. In Ethiopia, the prevalence of TBI is high, driven by factors such as road traffic incidents (RTIs), assaults, and falls. However, comprehensive data regarding the epidemiology, causes, severity, and outcomes of TBI in Ethiopia remain limited. This scarcity hinders the formulation of evidence-based interventions and policies that are specifically tailored to this context. Therefore, this systematic review and meta-analysis was conducted to provide pooled estimates on the prevalence, causes, severity, complications, and outcomes associated with TBI. Method A comprehensive review of existing literature was carried out by searching through PubMed, Scopus, Web of Science and EMBASE to gather studies published until September 2024. The inclusion criteria were centered on studies that discussed the frequency, causes, risk factors and results of brain injury, in Ethiopia. The quality of the studies included in the review was evaluated using the Joanna Briggs Institute (JBI) critical appraisal checklist. We utilized Stata 17 statistical software for analysis. To address the heterogeneity observed among the studies, random-effects models were employed. Results The pooled prevalence of TBI among patients presented with trauma was approximately 30.5%. The average age of the patients was 27.48 ± 2.047 years. The main causes for TBI were assaults 36% (CI: 0.28–0.44) road traffic incidents 35% (CI: 0.28–0.41) and falls 21% (CI: 0.15–0.27). Mild TBI made up 57% while moderate and severe TBI accounted for 25% and 18%, respectively. Complications, such as post-traumatic seizures and infections, were reported in 17% of cases. Additionally, the overall mortality rate was 12%. However, significant variability was observed among studies. Conclusion The meta-analysis underscores the impact of TBI, in Ethiopia with high mortality rates and associated challenges. The results underscore the pressing requirement for measures to decrease TBIs linked to accidents and violence while also enhancing emergency services access and strengthening neurosurgeons capabilities, in Ethiopian medical facilities.